Topographical distribution of the human brain to Plukenetia volubilis-based omega-3,6,9 enriched egg consumption - Phakkharawat Sittiprapaporn; Prayoon Suyajai (IAES International Journal of Artificial Intelligence (IJ-AI), 2022)
Docosahexaenoic acid (DHA) is related to cognitive development. Consumers' brain health could benefit from changes in the omega 6:3 ratio. This study aimed to examine how the Plukenetia volubilis-based omega-3,6,9 enriched egg supplementation affects electrical brain activity during the attention/inhibition (Go/NoGo) test. Healthy subjects (n = 20) were chosen at random to eat 2 boiled Plukenetia volubilis-based omega-3,6,9 enriched eggs for 12 weeks. The ePrime v.3.0 application recorded behavioral performance during the Go/NoGo test during the electroencephalographic recording. The finding of this study was that twelve weeks of boiled Plukenetia volubilis-based omega-3,6,9 enriched egg consumption significantly decreased the reaction time responses compared to the baseline. The topographical distribution revealed that the mean amplitude of N1 produced a slightly larger amplitude in the 12th week compared to the baseline. The P3 component, following N1, was also larger in the 12th week compared to the baseline. After 12 weeks of consuming the Plukenetia volubilis-based omega-3,6,9 enriched eggs, the central nervous system activities during a Go/NoGo test were believed to be enhanced.